A Smartphone App Shows Patients Return to Preoperative Gait Metrics 6 Weeks After Hip Arthroscopy, and Gait Metrics Have Low to Moderate Correlations With a Hip-Specific Patient-Reported Outcome Measure - Sachin Allahabadi, M.D; Thomas W. Fenn, B.S; Jordan H. Larson, B.S; David Zhu, M.D; Philip Malloy, Ph.D., P.T; Shane J. Nho, M.D., M.S (Elsevier, 2023)
Purpose: The purpose of this study was to use a smartphone app to collect gait metrics in patients undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and determine when gait metrics return to preoperative levels and if gait metrics correlate with postoperative hip-specific patient-reported outcomes. Methods: Patients undergoing primary hip arthroscopy for FAIS from August 2021 to December 2022 were prospectively enrolled. Patients downloaded the iPhone app, rHip, at ∼6 months postoperatively, enabling retroactive access to Apple Health data. Gait metrics included step count, step length, and walking speed. Each patient's preoperative baseline was compared to that individual's successive postoperative week metrics. All patients underwent a standard 4-stage rehabilitation protocol. We compared metrics from beginning to end of each phase (i.e., week 1 to 6 for phase 1) and evaluated correlations with patient outcomes. Results: Fifty patients (40 women; age: 31.9 ± 14.5 years) were included. Patients had significantly reduced step count from postoperative weeks 1 to 5 and improved upon baseline at weeks 13 and 16 to 26. Patients had significantly reduced step length from postoperative weeks 1 to 4 and improved upon baseline at weeks 16 and 20. Patients had significantly lower walking speed from postoperative weeks 1 to 6 and improved upon baseline at week 20 (P < .05). Step count significantly improved over phase 1 rehabilitation (P < .05). Step length and walking speed significantly improved over each of phases 1 to 3 (P < .05 for all). Preoperatively, weak correlations were noted between step length and Patient-Reported Outcomes Measurement Information System (PROMIS) for Physical Function (PF)/Pain, as well as walking speed and Hip Outcome Score-Activities of Daily Living (HOS-ADL)/PROMIS-Pain. At 3 months, moderate correlations were noted between step count and HOS-ADL/12-item international Hip Outcome Tool (iHOT-12), step length and HOS-ADL/PROMIS-PF, and walking speed and HOS-ADL/iHOT-12/PROMIS-PF/PROMIS-Pain. At 6 months, weak to moderate correlations were noted between all 3 gait metrics and HOS-ADL. Conclusions: A smartphone app was capable of capturing health data gait metrics. Patients undergoing hip arthroscopy for FAIS returned to baseline levels in step count, step length, and walking speed after phase 1 (6 weeks) of rehabilitation. The most consistent correlations between gait metrics and step count were seen at 3 months, although only weak to moderate. Gait metrics similarly had weak to moderate correlations with HOS-ADL at 6 months. Level of Evidence: Level IV, case series.